INFORMAL RELIGIOUS PRACTICES IN ADJARA: A SOCIAL ANALYSIS PERSPECTIVE - Irakli Manvelidze; Ineza Zoidze (International Journal of Innovative Technologies in Social Science, 2025)
This study examines the informal religious practices of the Muslim communities in Adjara, Georgia, with a particular focus on elements of Sharia law that have persisted as “silent norms.” The research aims to identify these Sharia elements, analyze their social functions, gender dimensions, and normative significance, and explore the hybrid normative environment created through their integration with local cultural traditions. Methodologically, the study employs a qualitative, interdisciplinary approach combining historical and comparative analysis, ethnographic fieldwork, semi-structured interviews with local elders and religious leaders, and documentary analysis. Ethical standards were strictly observed, ensuring respondent anonymity and informed consent. Data were analyzed through thematic coding and comparative analysis, allowing for a comprehensive understanding of the historical, social, and legal coexistence of Sharia norms in the region. The findings reveal that despite the formal abolition of Sharia institutions following Russian and Soviet rule, certain elements continue to function as informal norms within the community. These practices-encompassing marriage rituals (Aqdis Gachra), inheritance, funeral rites, oaths on the Quran, and other life-cycle ceremonies-play a significant role in maintaining social order, gender arrangements, community identity, and cultural memory. They represent a hybrid normative system where secular state standards and religious-cultural norms coexist and shape everyday social life. In conclusion, the study demonstrates that Adjara’s Muslim communities maintain historical religious heritage alongside contemporary social standards. Informal Sharia norms function not only as cultural and religious practices but also as mechanisms of social regulation, intercultural continuity, and community cohesion, illustrating a unique example of normative pluralism and cultural resilience.